Meningkatkan Kedisiplinan Mengerjakan Tugas Tepat Waktu Melalui Layanan Bimbingan Kelompok Pada Siswa Kelas XI IPS SMA Negeri 1 Matauli Pandan - Setyo Lelono (Medan State University, 2021)
This study aims to determine the condition of students before and after guidance and counselingservices are carried out using the group guidance model, as well as to determine the effectiveness of groupguidance services in improving the discipline of doing assignments from subject teachers on time. Theresearcher divides this action research into three parts, namely the initial activity of choosing class XI IPS asthe research sample because in this class the most violations occur. The results showed that in the initialconditions students who committed violations did not do assignments on time 7 times and above in class XIIPS as many as 8 students with the details of class XI IPS 1 as many as 3 students, class XI IPS 2 as many as3 students and class XI IPS 3 as many as 3 students. 2 students. The number of violations of the initialconditions before the BKp was carried out was 87 violations. After BKp cycle I there was a decrease in thenumber of violations by 37 (42.53%). In the BKp cycle II the number of violations decreased from 50 to 15violations, so that in the second cycle BKp there was a decrease in violations by 35 (70%). After the BKpcycle II, reflection was carried out and continued with the BKp cycle III. In cycle III BKp activities, thenumber of violations which was originally 15 decreased to 0 (100%) violations or no violations occurred.